Egyptian Objects in Buenos Aires: Amalia Lacroze de Fortabat Art Collection - Laporta, Virginia Gimena (2015)
The Fortabat Art Collection contains Egyptian objects from different periods, includingroyal inscriptions, anthropomorphic statues of goddesses such as Hathorand Wadjet, as well as several representations of deified animals: an ibis, a lion, acat and a bull, each of which might be associated with different gods (e.g. Thoth,Sekhmet, Bakhtet and Apis). Among the exhibited artifacts there is also a maskfrom the Ptolemaic period, with typical Egyptian stylistic traits influenced by theshapes and colors employed by Greek artisans.